An examination of the association between forced sex history and reproductive coercion experiences among Black women attending STD clinics in Baltimore, MD, USA - Danielle M. Campbell; Marguerite B. Lucea; Andrea N. Cimino; Jacquelyn C. Campbell; Jamila K. Stockman (BMC, 2023)
Abstract Background Reproductive coercion victimization (RCV) is a significant public health issue that negatively affects women's sexual and reproductive health outcomes. Less is known about reproductive coercion perpetration (RCP). Few studies have examined these phenomena among representative samples of Black women. Methods Retrospective data of women (n = 298) attending STD clinics in Baltimore, MD were analyzed. We calculated lifetime and 12-month prevalence reports of reproductive coercion, and reported values stratified by forced sex history. Binomial logistic regression models were used to examine the association between forced sex history and RCV, accounting for other types of violence typologies. Results Lifetime and past 12-month RCV and RCP prevalence were higher among women with forced sex experiences than their counterparts (Lifetime RCV: 46.9% versus 17.5%; past 12-month RCV: 19.4% versus 8.5%. Lifetime RCP: 24.5% versus 17%; past 12-month RCP: 13.3% versus 10.5%). Adjusted models, lifetime reproductive coercion: Women reporting forced sex had a 3.58 times higher odds of having had experienced RCV compared to women not reporting forced sex (AOR 3.58; 95% CI 2.00, 6.46). Women reporting forced sex had a 3.66 times higher odds of having ever experienced pregnancy coercion compared to their counterparts (AOR 3.66; 95% CI 1.93, 7.03) and 4.30 times higher odds of having ever experienced condom manipulation (AOR 4.30; 95% CI 2.15, 8.86). Adjusted models, past 12-month reproductive coercion: Women reporting forced sex had a 2.72 times higher odds of having had experienced past 12-month RCV compared to women not reporting forced sex (AOR 2.72; 95% CI 1.27, 5.91). Women reporting forced sex had a 3.25 times higher odds of having experienced past 12-month pregnancy coercion compared to their counterparts (AOR 3.25; 95% CI 1.38, 7.83) and 3.41 times higher odds of having experienced past 12-month condom manipulation (AOR 3.41; 95% CI 1.14, 10.98). Conclusions Participants in our study reported high rates of RCV. Our novel exploration revealed significantly high rates of co-occurring forced sex experiences and RCV and initial prevalence report of RCP. Agencies have a unique opportunity to intervene by implementing screening protocols and referrals for supportive services. These findings may inform future intervention research efforts aimed at improving reproductive health outcomes among Black women.